Origen e impacto socioeconómico de las remesas de los trabajadores en Colombia (2014)
Different socioeconomic situations have caused the international migration of Colombians nationals, among them, bettering the life quality of their families. The repatriation of earnings is done through different channels, being the most used payment over the counter –cash-. The impact of this situation is analysed on its macroeconomic aspects: participation in the gross domestic product (GDP), the liquidity of the economy represented in the monetary base, and its reflection in the intervention rate of the Central Bank, as well fluctuations in the exchange rate and the impact thereof.